A QoS-based network planning method for power fiber to the home - Shuai SHAO; Zhijun SHANG; Zhongfeng WANG; Guoliang XIN; Yueyue LI; Xiangyu KONG; Xujing PENG (Dianxin kexue)
A QoS-based network planning method for power fiber to the home was proposed.Firstly,the distribution structure of different buildings was combined to carry out targeted ODN line path design.Secondly,in the ONU packet cluster planning stage,in order to meet the QoS requirements of multi-service differentiation,the communication cost as the optimization goal was uesd,and the optimization problem model was established with the constraints of access capacity,reliability and delay.At the same time,intelligent algorithms were used to solve the optimization problem model.Finally,the optical path attenuation of the planned network was calculated to meet the actual application needs.The simulation results show that the proposed QoS-based network planning method for power fiber to the home can save network construction cost while ensuring service reliability and delay requirements.